Identification of hypoxia-related diagnostic biomarkers and immune signatures in diminished ovarian reserve - Song, Minxue; Ni, Lili; Ma, Zebing; Zhong, Xin; Liu, Yibing; Kuang, Jilin; Li, Ping (Frontiers in Genetics, 2025)
BackgroundDiminished ovarian reserve (DOR) becomes more common with age, and hypoxia is a key cause of apoptosis in ovarian granulosa cells. This study investigated the genetic links between hypoxia and DOR.MethodsThe GSE87201 dataset for DOR was sourced from Gene Expression Omnibus database, normalized for common differentially expressed genes (Co-DEGs), and identified Hypoxia-related differentially expressed genes (HRDEGs) via GeneCards; Receiver Operating Characteristic (ROC) curves evaluated HRDEGs’ diagnostic value, and protein-protein interaction networks were visualized with STRING and Cytoscape. Enrichment analyses included Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and immune cell infiltration compared ovarian reserve groups. A granulosa cell injury model was created using 4-hydroperoxycyclophosphamide (4-HC), with Quantitative real-time PCR and Western blot measuring FANCI and KAT2A expression, and Cell Counting Kit-8 assays and flow cytometry assessing cell proliferation and apoptosis.ResultsTwelve hypoxia-related genes were differentially expressed between low ovarian reserve (LOR) and high ovarian reserve (HOR), with 17 linked to DOR; eight pathways differed between LOR and HOR. Six hub genes (FANCI, KAT2A, TACC3, TPX2, VHL, WSB1) were enriched in Fanconi anemia and HIF-1 pathways, affecting microtubules, spindle formation, and cytoskeleton dynamics during mitosis. Immune cell infiltration analysis showed significant differences, with FANCI, TACC3, and TPX2 correlating with immune populations. The DOR group had increased FANCI and KAT2A levels compared to Control (two of the several genes that were matched were randomly selected for validation), alongside reduced cell viability and increased apoptosis.ConclusionFANCI, KAT2A, TACC3, TPX2, VHL, and WSB1 may be diagnostic biomarkers for DOR, providing novel insights for future research into the pathogenesis of hypoxia-induced DOR.